Flow analysis of melted urea in a perforated rotating bucket - Muhammad, A. (2013)
A comprehensive study of the internal flow field for the prilling application in a perforated rotating bucket has been carried out. Computational Fluid Dynamics (CFD) is used to investigate the flow field of urea melt inside the perforated rotating bucket. The bucket is mounted at the top of the prilling tower. In prilling process, urea melt is sprayed by the perforated rotating bucket to produce the urea droplets, which falls down due to gravity. These drops fall down through a cooling medium and solidify into prills. The velocity field in the bucket is very important to study, as it has great effect on the heat and mass transfer performance in prilling process. ANSYS 14.0 CFD package is used to simulate and Design Modeler and Catia V5 are used for geometrical model of the perforated prilling bucket. Velocity distribution on different planes are obtained and discussed. Â© (2013) Trans Tech Publications, Switzerland.